Switch mode power supply with flyback LED driver topology in public lighting systems energy supply - Widjonarko, Widjonarko; Hardianto, Triwahju; Akmal, Ahmad Ishamul Ayady; Ate, Abdelrahim Ahmed Mohammed (International Journal of Power Electronics and Drive Systems (IJPEDS), 2023)
This research aims to design a flyback topology switch-mode power supply constant voltage and constant current light emitting diode (LED) driver to improve the performance of the LED. The flyback topology is chosen for its simple design and small size and uses high-frequency switching to lower the high DC voltage from the power source. The research aims to avoid blackouts caused by a drop in the power source voltage and to produce technological products that can be developed for other lighting applications. The constant-voltage feedback system ensures that the current flowing to the LED remains stable despite changes in load or other conditions. When there is a voltage drop from the power source, this topology can maintain the voltage and current stable and in accordance with the working voltage specifications of the LEDs. According to test results, the LED driver's output voltage ranges from 18.03 to 18.06 volts with an average message error value of 0.3%. In this system, switching occurs at frequencies ranging from 18.041 Hz to 38.230 Hz. With a constant current value of 0.58 ampere, the resulting lamp's lux value is stable and does not significantly change.